Information technology and public administration modernization in a developing country: Pursuing paperless clearance at Ghana customs. (10th October 2021) - Addo, Atta
Abstract: Despite significant information technology (IT) implementations in public administrations of developing countries to change their dysfunctional traditional practices towards modern forms, the outcomes are typically disappointing relative to the potential of IT for organizational change. With a case study of the customs clearance process when importing goods through Ghana's main port, the Tema Harbour, we explore why IT struggles to modernize traditional practices of public administration in a developing country context. We focus on explaining the persistence of paper use at Ghana customs despite more than a decade of digitalization and automation to establish paperless processes that eliminate malpractices of traditional clearance. We view modernization as a process of long‐term institutional change and therefore draw from the literature on IT and institutional change to focus our investigation on the dynamics of incongruent institutional logics of IT and public administration. We show that in the administration context of a developing country like Ghana, the endurance of patrimonial logics in the state and broader society, coupled with high levels of administrative discretion and ambivalent or weak compliance pressure limit the realization of IT for modernization and allows hybrid practices to emerge.